Microbial Neuraminidase Induces a Moderate and Transient Myelin Vacuolation Independent of Complement System Activation - Granados-Durán, Pablo (Front Neurol, 2017)
AIMS: Some central nervous system pathogens express neuraminidase (NA) on their surfaces. In the rat brain, a single intracerebroventricular (ICV) injection of NA induces myelin vacuolation in axonal tracts. Here, we explore the nature, the time course, and the role of the complement system in this damage. METHODS: The spatiotemporal analysis of myelin vacuolation was performed by optical and electron microscopy. Myelin basic protein-positive area and oligodendrocyte transcription factor (Olig2)-positive cells were quantified in the damaged bundles. Neuronal death in the affected axonal tracts was assessed by Fluoro-Jade B and anti-caspase-3 staining. To evaluate the role of the complement, membrane attack complex (MAC) deposition on damaged bundles was analyzed using anti-C5b9. Rats ICV injected with the anaphylatoxin C5a were studied for myelin damage. In addition, NA-induced vacuolation was studied in rats with different degrees of complement inhibition: normal rats treated with anti-C5-blocking antibody and C6-deficient rats. RESULTS: The stria medullaris, the optic chiasm, and the fimbria were the most consistently damaged axonal tracts. Vacuolation peaked 7 days after NA injection and reverted by day 15. Olig2+ cell number in the damaged tracts was unaltered, and neurodegeneration associated with myelin alterations was not detected. MAC was absent on damaged axonal tracts, as revealed by C5b9 immunostaining. Rats ICV injected with the anaphylatoxin C5a displayed no myelin injury. When the complement system was experimentally or constitutively inhibited, NA-induced myelin vacuolation was similar to that observed in normal rats. CONCLUSION: Microbial NA induces a moderate and transient myelin vacuolation that is not caused either by neuroinflammation or complement system activation.